Future Directions and Considerations for Talent Identification in Australian Football - Bonney, Nathan; Larkin, Paul; Ball, Kevin (Frontiers in Sports and Active Living, 2020)
As the focus on the elite Australian Football League competition becomes greater so too does the demand for success. Clubs are heavily scrutinised for their draft selections and as such are taking more interest in the younger levels of competition in an attempt to identify and monitor talent. Based on contemporary talent identification knowledge, this review examines the current talent identification process in Australian football, with a focus on areas to potentially improve or inform future developments. Currently, a significant gap exists between static and isolated assessment procedures used to identify talent in Australian football and the dynamic nature of match play. Future assessments should consider factors such as maturation, fatigue and ecological dynamics. The addition of a valid and reliable technical skill assessment (e.g., a small-sided game) to the current Australian Football League draft combine was recommended.